2019
DOI: 10.1007/s11356-019-05063-8
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal noise and habitat homogeneity limit species richness of owls in an urban environment

Abstract: Habitat loss and fragmentation are listed among the most significant effects of urbanization, which is regarded as an important threat to wildlife. Owls are the top predators in most terrestrial habitats, and their presence is a reliable indicator of ecosystem quality and complexity. However, influence of urbanization on owl communities, anthropogenic noise in particular, has not been investigated so far. The aim of this study was to identify the role of noise and landcover heterogeneity in the species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…Our findings also show that the Mottled Owl tends to be in less noisy sites across the city. These results agree with the growing body of evidence of the negative impacts of noise on habitat occupation and life history of birds in urban settings (Francis et al 2009;Patón et al 2012;Luther and Gentry 2013;Slabbekoorn 2013), as well as recent studies suggesting decreases of owl species richness with high nocturnal noise levels (Fröhlich and Ciach 2019). Given that most birds depend on the acoustic channel for communication, anthropogenic noise acts as an environmental filter by limiting species presence according to their tolerance to noise (González-Oreja 2017; Manzanares Mena and Macías Garcia 2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings also show that the Mottled Owl tends to be in less noisy sites across the city. These results agree with the growing body of evidence of the negative impacts of noise on habitat occupation and life history of birds in urban settings (Francis et al 2009;Patón et al 2012;Luther and Gentry 2013;Slabbekoorn 2013), as well as recent studies suggesting decreases of owl species richness with high nocturnal noise levels (Fröhlich and Ciach 2019). Given that most birds depend on the acoustic channel for communication, anthropogenic noise acts as an environmental filter by limiting species presence according to their tolerance to noise (González-Oreja 2017; Manzanares Mena and Macías Garcia 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In comparison to diurnal species, the ecological response of nocturnal birds to urbanization has not been well studied because of their low density and detectability (Weaving et al 2011;Isaac et al 2013;Fröhlich and Ciach 2019). Among nocturnal birds, owls are particularly interesting given their role as top predators in most terrestrial habitats, with their presence often being related to ecosystem quality (Isaac et al 2013;Fröhlich and Ciach 2019). Actually, in some urban areas owls have been identified as important biological control agents of rodent pests (Saufi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their methods did not test whether prey, once detected, are made easier to catch by the elevated background sound, as predicted by the stealth hypothesis. Some ecological studies found a negative correlation between owl diversity and abundance in habitats with high levels of anthropogenic sound ( Fröhlich and Ciach 2018 , 2019 ), implying owls avoid noisy environments, as predicted by the self-masking model but not the stealth model; but others have not found this pattern ( Shonfield and Bayne 2017 ).…”
Section: How Owls Huntmentioning
confidence: 98%
“…2). While indicating the sites' importance to breeding raptors, it potentially reflects a bias in sampling effort arising from their accessibility to the researchers and public as most of the studies required either physical inspection of the nest sites or for observations to be made from accessible locations (Rutz 2008;Sumasgutner et al 2014b;Fröhlich and Ciach 2019). Raptors nesting around areas highly frequented by people, whether they are in green spaces or "out of place", are likely to draw citizens' attention (Philo and Wolch 1998;Khoo and Lee 2020), making them vulnerable to human disturbance (Chace and Walsh 2006;Sorace and Gustin 2010).…”
Section: Raptor Habitat Use In the Urban Environmentmentioning
confidence: 99%